MENDETEKSI KECURANGAN LAPORAN KEUANGAN: PERSPEKTIF FRAUD HEXAGON THEORY - Sumardin, Hervina; Rusman Soleman; Mahardika Catur Putriwana Malik (Juremi: Jurnal Riset Ekonomi, 2025)
Financial reports play an important role in describing the company's position and performance and supporting stakeholder decision-making. However, manipulation often occurs to benefit management, which leads to fraud and harms various parties. This case is increasingly prevalent in the health sector due to pressure to achieve targets, market expectations, and tight competition. Companies experiencing financial difficulties often hide their true conditions. This phenomenon poses a great risk to investors and has the potential to damage public trust in the industry. The purpose of this study is to detect financial report fraud using the fraud hexagon theory in health companies listed on the Indonesia Stock Exchange in 2019-2023. The data collection method uses a purposive sampling technique. There are 17 companies that meet the criteria as samples, so that the research data totals 85. The type of data used is quantitative data obtained from the company's annual financial report. The technique used in this study is the panel data regression analysis technique using the E-Views 13.0 statistical test tool. The results of the study indicate that financial stability, change in auditor, change in director, arrogance, collusion do not affect financial statement fraud. While financial targets, external pressure, and nature of industry affect financial statement fraud